AUSTRALIAN LITERARY CRITICISM - Donny Syofyan (Universitas Muara Bungo, 2022)
The Australian literacy criticism has focused mostly on the gender issues, preferably the discrimination of women in the society. However, critics are not only biased in their work based on their gender, but also fail to agree on the most appropriate method of critiquing; individual or collective. This is unlike Indonesian critics where they embrace communal criticism as it contributes to positive change to the society. The failure to have clear-cut perspective on which criticism method should be appropriate shows that there is a significant gap that needs to be filled, thus necessitating the current study.